Arthur Dulay and John Grierson: Fitting Drifters (1929). Issue 3 (2nd September 2019) - Izod, John
Abstract : The moment when Grierson's Drifters film was first screened to audiences at the end of 1929 coincided with the technological transition in British cinema from accompaniment by musicians playing live in the auditorium to the introduction of fully synchronized sound on film. Arthur Dulay's 'Musical Suggestions for Drifters ' furnish plain evidence of not only how complex the work of projectionists and their assistants could be, but also how, until the transition to recorded sound was complete, a variety of methods were deployed in different cinemas to add music and sound effects to pictures.